3‐Year Randomized Controlled Prospective Clinical Trial on Different CAD‐CAM Implant Abutments. (14th March 2016) - Ferrari, Marco; Tricarico, Maria Gabriella; Cagidiaco, Maria Crysanti; Vichi, Alessandro; Gherlone, Enrico Felice; Zarone, Fernando; Sorrentino, Roberto
Abstract: Background: Zirconia abutments were introduced to restore esthetic regions and showed sufficient stability to support implant restorations. Nonetheless, to date the observation periods are shorter than those of titanium abutments. Purpose: To assess the survival of implant crowns supported by computer aided design‐computer aided manufacturing (CAD‐CAM) abutments after 3 years. Materials and Methods: Fifty‐six patients were selected for this prospective clinical study. Each patient received at least 1 titanium implant for a total of 89 fixtures. A two‐stage surgical technique and no additional soft or hard tissue graft were used. The implants were randomly divided into 3 groups receiving different CAD‐CAM abutments: titanium, titanium nitride, and zirconia. Zirconia or metal‐ceramic crowns were used as final restorations. Cementation was the baseline and the restorations were checked after 6 months, 1, 2, and 3 years, assessing any mechanical complication. Statistical analyses were performed to evaluate the 3‐year success rates. Results: Five failures were reported in the zirconia group; all the failed restorations showed fractures of the abutment connection. Four failures occurred in posterior regions and one more occurred while screwing the abutment. Titanium and titanium nitride abutments had significantly higher 3‐year success rates than zirconia abutments ( p < .05). Conclusions: Atlantis titanium and titanium nitride abutments showed optimal clinical performances after 3 years. Conversely, Atlantis zirconia abutments should be avoided to restore posterior regions.